Implementasi Sistem Informasi Pendaftaran Online Berbasis Web Pada SMP S Sinar Bijaksana Guang Ming - Putri, Della Utami; Fachruddin; Jasmir (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
SMP S Sinar Bijaksana Guang Ming is a private school that prioritizes character education while also emphasizing knowledge and soft skills development. Currently, SMP S Sinar Bijaksana Guang Ming has not yet implemented an effective information system, as the registration process requires parents of prospective students to register directly at the school and return for interviews and entrance exams. Registration data is still stored using Microsoft Excel. This traditional method presents challenges such as delays in data entry, file corruption, and difficulties in generating reports. Therefore, the author feels the need for computerization in the student registration information system to simplify the registration process for prospective students without having to visit the school, and to make the admin's tasks more efficient and effective. To address this issue, the author proposes the design and implementation of a Web-Based Online Registration Information System at SMP S Sinar Bijaksana Guang Ming. The system development method used is the waterfall model. This research produces a web-based online registration information system where administrators can manage and print data related to the gallery, teachers, student registrations, interview results, and written exam results. Parents of prospective students can view information about teaching staffs, school activities, and available facilities, as well as completing the registration process and checking the results of interviews and written exams. Meanwhile, the principal can search for and print reports on student registrations, interview results, and written exam results. Furthermore, this system is expected to provide convenience for all parties, from admins to parents of prospective students, in the registration process and data management.